2015
DOI: 10.1021/cs502006x
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dual-Catalytic Cascade by Chiral N-Heterocyclic Carbene and Quinuclidine: Mechanism and Origin of Enantioselectivity in Benzofuranone Formation

Abstract: Contemporary literature offers a number of interesting examples for asymmetric multicatalytic reactions using chiral N-heterocyclic carbenes (NHCs) in conjunction with other catalysts. One of the very recent examples demonstrated a convenient strategy toward realizing chiral benzofuranones from salicylaldehyde and dimethyl acetylenedicarboxylate (DMAD). In this article, we report the mechanism and insights on the origin of asymmetric induction as obtained through a comprehensive density functional theory (M06-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 89 publications
0
29
0
Order By: Relevance
“…From Table , although the yields of the reactions were limited to approximately 80 % due to the formation of side pro‐duct chromene derived from intramolecular aldol of intermediate enolates, it was found that both electron‐rich and electron‐deficient salicylaldehydes with electron‐withdrawing and electron‐donating groups participated in homogeneous asymmetric Michael/Stetter sequence to afford the corresponding products in moderate to good yields (62–84 %) and good to excellent enantioselectivities (83–96 %ee). Similar to the ever‐reported homogeneous catalytic results, the lowest yields were observed for ortho ‐substituted salicylaldehydes, which resulted from the steric hindrance of ortho ‐substituents to nucleophilic addition.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From Table , although the yields of the reactions were limited to approximately 80 % due to the formation of side pro‐duct chromene derived from intramolecular aldol of intermediate enolates, it was found that both electron‐rich and electron‐deficient salicylaldehydes with electron‐withdrawing and electron‐donating groups participated in homogeneous asymmetric Michael/Stetter sequence to afford the corresponding products in moderate to good yields (62–84 %) and good to excellent enantioselectivities (83–96 %ee). Similar to the ever‐reported homogeneous catalytic results, the lowest yields were observed for ortho ‐substituted salicylaldehydes, which resulted from the steric hindrance of ortho ‐substituents to nucleophilic addition.…”
Section: Resultsmentioning
confidence: 99%
“…Of particular note was that both mesopore‐abundant HMOPNs‐supported Rovis catalyst and mesopore‐deficient PS‐7 promoted the Stetter reaction of salicylaldehyde (R=H) with the sharply decreased enantioselectivities with 7–8 %ee decrements, compared with homogeneous Rovis catalyst (93 %ee) (Table ). It was ever‐reported that the enantioselectivities of products appeared to be independent of steric or electronic factors of substituted salicylaldehydes, and its enantiocontrol was exerted by a network of noncovalent interactions between Rovis catalyst and substrates . Therefore, it was conjectured that the anchorage of Rovis catalyst into solid affected the noncovalent interactions such as π…π stacking interaction between the N‐aryl(C 6 F 5 ) group and salicylaldehyde moiety, and resulted in the increased cis ‐( re , si )‐ transition state of Breslow intermediate leading to a S configuration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations